Etika Pendidikan Agama Kristen Sebagai Pilar Dalam Membangun Karakter Siswa Yang Berlandaskan Nilai Kristiani - Lende, Stefani Natalia; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2025)
Abstract: Character education has become a central issue in the world of modern education, given the rampant moral degradation among the younger generation, especially today's schoolchildren. In this context, Christian Religious Education has a strategic role as a means of fostering values and ethics rooted in the teachings of Christ. Unfortunately, the approach to religious education is often still cognitive and has not touched the dimensions of character building holistically. The phenomenon of weak integration between the teaching of faith and the formation of real behaviour in Christian schools shows the need for renewal in the pedagogical approach. This research aims to analyse how ethics in Christian Religious Education can serve as the main pillar in building students' character that reflects Christian values. This research uses a descriptive qualitative method with a literature study approach and curriculum document analysis. The results of the study show that the integration of the values of love, justice, humility, and responsibility in the learning process can strengthen the formation of Christian character. Ethics instilled through religious teaching becomes a moral foundation that guides students in making the right decisions amidst the challenges of the times. Therefore, Christian Religious Education not only forms the knowledge of faith, but also becomes an effective tool in growing a whole person with integrity.Keywords: Christian Religious Education, Ethics, Student Character, Christian Values, Moral Formation Abstrak: Pendidikan karakter menjadi isu sentral dalam dunia pendidikan modern, mengingat maraknya degradasi moral di kalangan generasi muda terutama naradidik sekolah dewasa ini. Dalam konteks ini, Pendidikan Agama Kristen memiliki peran strategis sebagai sarana pembinaan nilai dan etika yang berakar pada ajaran Kristus. Sayangnya, pendekatan pendidikan agama seringkali masih bersifat kognitif dan belum menyentuh dimensi pembentukan karakter secara holistik. Fenomena lemahnya integrasi antara pengajaran iman dan pembentukan perilaku nyata di sekolah-sekolah Kristen menunjukkan perlunya pembaruan dalam pendekatan pedagogis. Penelitian ini bertujuan untuk menganalisis bagaimana etika dalam Pendidikan Agama Kristen dapat berfungsi sebagai pilar utama dalam membangun karakter siswa yang mencerminkan nilai-nilai Kristiani. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur dan analisis dokumen kurikulum. Hasil kajian menunjukkan bahwa integrasi antara nilai kasih, keadilan, kerendahan hati, dan tanggung jawab dalam proses pembelajaran dapat memperkuat pembentukan karakter Kristiani. Etika yang ditanamkan melalui pengajaran agama menjadi landasan moral yang menuntun siswa dalam pengambilan keputusan yang benar di tengah tantangan zaman. Oleh karena itu, Pendidikan Agama Kristen tidak hanya membentuk pengetahuan iman, tetapi juga menjadi sarana efektif dalam menumbuhkan pribadi yang utuh dan berintegritas.